PENGARUH PROFITABILITAS, LIQUIDITAS, LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2015 - 2019) - Rizka Ariyanti; Muhammad Iqbal Notoatmojo; Okti Kusuma Dewi (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
This study aims to obtain information about the effect of Profitabilty, liquidity, Leverage and institutional ownership on tax avoidance. The factors tested in this study are Profitabilitas, Liquiditas, Leverage, institutional ownership as independent variables. While Tax Avaoidance as the dependent variable. This research is a research with a quantitative approach. The variables in this study consist of Profitability, Liquidity, Leverage and institutional ownership and Tax Avoidance. The population in this study were 11 companies in the food and beverage sector in 2015-2019. Data collection techniques by providing data collection techniques with the documentation method through the IDX official website were analyzed using multiple linear regression with SPSS software version 22. The results of hypothesis testing indicate that the independent variables simultaneously affect tax avoidance. Partially, Profitability has no effect on tax avoidance, Liquidity has a negative coefficient on tax avoidance. Leverage has no effect on tax avoidance, and institutional ownership has a positive and significant effect on tax avoidance.